Dynamic thermal performance of building components and application to the experimental and theoretical analysis of a ventilated façade - Marinosci, Cosimo <1974> (Alma Mater Studiorum - Università di Bologna, 2011)
The general aim of this work is to contribute to the energy performance assessment of ventilated façades by the simultaneous use of experimental data and numerical simulations. A significant amount of experimental work was done on different types of ventilated façades with natural ventilation. The measurements were taken on a test building. The external walls of this tower are rainscreen ventilated façades. Ventilation grills are located at the top and at the bottom of the tower. In this work the modelling of the test building using a dynamic thermal simulation program (ESP-r) is presented and the main results discussed. In order to investigate the best summer thermal performance of rainscreen ventilated skin façade a study for different setups of rainscreen walls was made. In particular, influences of ventilation grills, air cavity thickness, skin colour, skin material, orientation of façade were investigated. It is shown that some types of rainscreen ventilated façade typologies are capable of lowering the cooling energy demand of a few percent points.